The inner voice - James Ridgway, Anthony (International Journal of English Studies, 2009)
The inner voice- we all know what it is because we all have it and use it when we are thinking or reading, for example. Little work has been done on it in our field, with the notable exception of Brian Tomlinson, but presumably it must be a cognitive phenomenon which is of great importance in thinking, language learning, and reading in a foreign language. The inner voice will be discussed as a cognitive psychological phenomenon associated with short-term memory, and distinguished from the inner ear. The process of speech recoding will be examined (the process of converting written language into the inner voice) and the importance of developing the inner voice, as a means of both facilitating the production of a new language and enhancing the comprehension of a text in a foreign language, will be emphasized. Finally, ways of developing the inner voice in beginning and intermediate readers of a foreign language will be explored and recommended.